Minat beli skincare: Peran electronic word of mouth di Tiktok - Alodia Lastri Dwiputri; Syahputra Syahputra (Universitas Kristen Maranatha, 2023)
Product for taking care of our skin or skincare products, are one of the most traded products internationally and account for 36,1percent of the total cosmetic export and import globally products including to Indonesia. There are many skincare companies that do marketing and utilize electronic word of mouth (e-WOM) using social media. With the aim of determining the influence of e-WOM (quality, quantity, and credibility) in Tiktok on the purchase intention of skincare X products, this study was conducted by collecting research data through the distribution of questionnaires and sampling as many as 445 respondent using the purposive sampling methods. The method that used for analysis is a multiple regression analysis test and is processed by SPSS 26 software. The results of the study for descriptive analysis show that e-WOM quality and credibility are in the good category, while e-WOM quantity is very good. Judging from the data regarding multiple linear regression analysis, simultaneously e-WOM quality, quantity, and credibility have a positive and significant effect on the buying interest of skincare X products, but partially only e-WOM quantity does not have a significant effect. Based on the coefficient of determination test, it shows the influence of electronic word of mouth (e-WOM) quality, quantity, and credibility on purchase intention by 48,5 percent. This research can be used by companies to increase consumer buying interest by promoting with e-WOM and focusing on the quality, quantity, and credibility of e-WOM.